2005
DOI: 10.1007/s00234-005-1358-8
|View full text |Cite
|
Sign up to set email alerts
|

White matter lesions in watershed territories studied with MRI and parenchymography: a comparative study

Abstract: Brain aging affects an increasing segment of the population and the role of chronic cerebrovascular disease is considered to be one of the main parameters involved. For this purpose we compared retrospectively MRI data with digitized subtraction angiography (DSA) data in a group of 50 patients focusing onto the watershed area of the carotid artery vascular territories. In order to evaluate the presence of white matter lesions (WML) in the hemispheric watershed areas, coronal fluid-attenuated inversion-recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…Broad C5 upregulation might suggest a lower susceptibility threshold for white matter, rather than an anatomically specific regional pathology. This is consistent with the characteristic pattern of cerebral hypoperfusion secondary to carotid artery stenosis, which typically causes ischemic changes in watershed vascular territories[38]. Astrocyte and microglial activation within the corpus callosum suggests an inflammatory process.…”
Section: Discussionsupporting
confidence: 81%
“…Broad C5 upregulation might suggest a lower susceptibility threshold for white matter, rather than an anatomically specific regional pathology. This is consistent with the characteristic pattern of cerebral hypoperfusion secondary to carotid artery stenosis, which typically causes ischemic changes in watershed vascular territories[38]. Astrocyte and microglial activation within the corpus callosum suggests an inflammatory process.…”
Section: Discussionsupporting
confidence: 81%
“…The reasons underlying the asymmetry are unclear, but are likely related to the relative perfusion difference between the left and right hemispheres. Asymmetrical injury to WM in the watershed areas shows a very high correlation with cerebrovascular insufficiency . In addition, it has been suggested that the left hemisphere may be more vulnerable than the right to detrimental influences, including hypoxia .…”
Section: Discussionmentioning
confidence: 69%
“…Asymmetrical injury to WM in the watershed areas shows a very high correlation with cerebrovascular insufficiency. 33 In addition, it has been suggested that the left hemisphere may be more vulnerable than the right to detrimental influences, including hypoxia. 34 In our study sample, all of the 29 participants were right-handed, which may also be a contributing factor to the observed asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…The biological pathway of the indirect mechanisms remains unclear. Stenosis of small cerebral vessels, especially in the watershed areas29 and high metabolic demands of oligodendrocytes of associative WM contribute to a high vulnerability of the frontal WM to the indirect PWE mechanism30. Oligodendrocytes of the associative frontal WM are among the most metabolically active cells in the adult CNS and therefore, are highly susceptible to damages from hypoxia30.…”
Section: Discussionmentioning
confidence: 99%